The accountability and audit of governments : a comparative study - Normanton, E. L. (New York : Praeger, 1966)
This book reveals that without audit, no accountability and without accountability no control and if no control where is the seat of power?
Includes bibliographical references, index
MF23/01/2019
Loans
Keywords: Auditing; Finance, Public